Cdc28 tyrosine phosphorylation and the morphogenesis checkpoint in budding yeast. - Sia, R A (1996)
A morphogenesis checkpoint in budding yeast delays nuclear division (and subsequent cell cycle progression) in cells that have failed to make a bud. We show that the ability of this checkpoint to delay nuclear division requires the SWE1 gene, encoding a protein kinase that inhibits the master cell cycle regulatory kinase Cdc28. The timing of nuclear division in cells that cannot make a bud is exquisitely sensitive to the dosage of SWE1 and MIH1 genes, which control phosphorylation of Cdc28 at tyrosine 19. In contrast, the timing of nuclear division in budded cells does not rely on Cdc28 phosphorylation, suggesting that the morphogenesis checkpoint somehow turns on this regulatory pathway. We show that SWE1 mRNA levels fluctuate during the cell cycle and are elevated in cells that cannot make a bud. However, regulation of SWE1 mRNA levels by the checkpoint is indirect, acting through a feedback loop requiring Swe1 activity. Further, the checkpoint is capable of delaying nuclear division even when SWE1 transcription is deregulated. We propose that the checkpoint delays nuclear division through post-translational regulation of Swe1 and that transcriptional feedback loops enhance the efficacy of the checkpoint.